The impact of the Asian financial crisis on bank efficiency: the 1997 experience of Malaysia and Thailand - Sufian, Fadzlan (John Wiley & Sons, 2010)
In the mid-1990s, the East Asian countries experienced severe financial crisis that were followed by deep economic downturns. A variety of methodologies have been used to understand the nature of the Asian financial crisis. However, the impact of the 1997 Asian financial crisis on the efficiency of the financial industry has yet to be studied. By employing the Data Envelopment Analysis (DEA) approach the present study attempts to examine for the first time the impact of the 1997 Asian financial crisis on the efficiency of the Malaysian and Thailand banking sectors, two of the East Asian countries that were severely affected by the crisis. The study focuses on three major approaches vis., intermediation, value added and operating approaches. The results clearly bring forth the high degree of inefficiency in the Malaysian and Thailand banking sectors, particularly a year after the crisis. We .nd that the Malaysian banking sector has exhibited a higher TE levels during the post crisis period under the intermediation and value added approaches, while TE seems to be lower under the operating approach. The empirical findings suggest that the Thailand banking sector has exhibited a lower TE level during the post crisis period under all approaches.